Verbal Aggressive Behaviours of Elementary School Age Children - Pipit Festi Wiliyanarti1 , Rabiatul Awaliyah1 , Hariyono2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Verbal abuse has negative effects that will ultimately affect child development. Verbalabuse committed by parents may potentially leave a trauma in children’s lives and affect their growth anddevelopment. Children’s social environment where they carry out interactions may be the factor of verbalabuse of children.Methods: The design of this study is cross-sectional, with total population of 328 children of school age.259 children were selected with proportional random sampling technique. The independent variables wereparental verbal abuse and psychosocial factors, while the dependent variable was children verbal aggressivebehaviors. The instrument used was questionnaire sheets. The analysis performed was Logistic RegressionAnalysis.Results: Verbal abuse behaviors were influenced by parental verbal abuse factor (p=0.003) and psychosocialfactor (p=0.03).Conclusions: Parenting style and children’s social environment contribute to the probability of childrenverbal abuse. Family intervention is highly expected to prevent aggressive child behavior.